2020
DOI: 10.1177/1945892420958549
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Rhinosinusitis After Endoscopic Transsphenoidal Adenomectomy

Abstract: Objective Patients undergoing endoscopic transsphenoidal adenomectomy (eTSA) for pituitary tumors are at risk for postoperative complications, including rhinosinusitis. We aimed to determine if preoperative sinonasal disease is a risk factor for postoperative rhinosinusitis (PRS). Study Design Retrospective review. Setting Tertiary academic center in U.S. Subjects and Methods Patients with a diagnosis of pituitary adenoma who underwent eTSA between 2007-2016. PRS patients were matched to non-PRS patients or se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Interestingly, a recent study reported that prior sinonasal surgery might be associated with an increased risk of developing postoperative rhinosinusitis. Of notice, this was only significant in univariate and not in multivariable analyses 150 .…”
Section: Predictive Factors For Postoperative Sinonasal Deteriorationmentioning
confidence: 77%
See 1 more Smart Citation
“…Interestingly, a recent study reported that prior sinonasal surgery might be associated with an increased risk of developing postoperative rhinosinusitis. Of notice, this was only significant in univariate and not in multivariable analyses 150 .…”
Section: Predictive Factors For Postoperative Sinonasal Deteriorationmentioning
confidence: 77%
“…Reported postoperative nasal symptoms include rhinosinusitis, olfactory impairment, synechia, septal perforations, epistaxis, nasal congestion, and an unpleasant nasal smell [144][145][146][147][148][149][150] . In many studies, decreased sinonasal quality of life is seen mostly during the first weeks after surgery and then approaches baseline levels after 3-6 months [147][148][149][151][152][153] .…”
Section: Sinonasal Outcomementioning
confidence: 99%
“…In a study investigating risk factors for postoperative rhinosinusitis (PRS) after transsphenoidal adenohypophysectomy (TSA), Lee et al 8 posited preoperative sinonasal disease may portend higher risk for PRS. In a retrospective review and analysis of 987 patients, 49 developed PRS.…”
Section: Olfaction and Beyond: Advancing Our Understanding For Evidence-based Practicementioning
confidence: 99%